Controversies and challenges in the pathologic examination of lung resection specimens after neoadjuvant treatment. (April 2021) - Weissferdt, Annikka; Pataer, Apar; Swisher, Stephen G; Heymach, John V; Gibbons, Don L; Cascone, Tina; Sepesi, Boris
Highlights: Highlights the problems and challenges of pathologic examination of resected NSCLC in the era of neoadjuvant chemo and/or immunotherapy. The handling and interpretation of such cases is not well defined and current guidelines are largely based not evidence-based. Many clinical trials rely on pathologic response as a surrogate endpoint of efficacy for novel neoadjuvant agents. Lack of a standardized approaches raises concerns about the validity, reproducibility and comparability of the results of clinical trials. Discusses the difficulties encountered during pathologic examination of such specimens and critically reviews recently published guidelines. Abstract: New therapy approaches in the treatment of surgically resectable non-small cell lung cancer (NSCLC) challenge the traditional handling and examination of pathology specimens. The increasingly common use of neoadjuvant therapies before surgical resection, due to advantages in novel drug administration, tolerance, and measurement of radiographic and pathologic response compared to adjuvant treatment, has the potential to alter the microscopic tumor appearance and its biology. Currently, many clinical trials use pathologic response as a surrogate endpoint of clinical efficacy, since the extent of residual viable tumor appears to correlate with outcome in patients treated with neoadjuvant chemotherapy. Consequently, pathologic assessment of the extent of residual viable tumor is of paramount importance. However, high level evidence-based guidelines on how to process and evaluate such specimens are lacking. Moreover, while pathologic response has been shown to be associated with survival after chemotherapy, its significance after immunotherapy remains to be determined. Additionally, many clinical trials do not routinely include pathologists in trial design, which may lead to non-standardized evaluation of pathologic response. Although recently, several algorithms have been proposed to address these issues, none of them represents evidence-based recommendations or is universally applied. Therefore, controversies and challenges continue to exist, raising concerns about the validity, reproducibility, and comparability of the results of many neoadjuvant clinical trials. Herein, we discuss the current difficulties in pathologic specimen evaluation following neoadjuvant therapy in NSCLC and propose potential approaches to overcome these challenges.